Relationship between the chemical composition, physical, technological, and sensory properties of beef and the colour of muscle tissue - O. Kruk; A. Ugnivenko (Тваринництво та технології харчових продуктів, 2024)
In Japan, the United States, Korea, and Australia, the colour of muscle tissue is used to assess the quality of beef carcasses, while in the EU and Ukraine, this feature is not considered. The relevance of the study was to substantiate the need to consider the colour of muscle tissue to assess the consumer properties of beef. The purpose of the study was to evaluate the chemical composition, sensory and physical, and technological properties of beef in accordance with the colour of muscle tissue. The study used carcasses of 21-month-old bulls (n=13) of Ukrainian blackand-white dairy cattle slaughtered after a 24-hour fast with free access to water in a slaughterhouse (Kalynivka village) in Brovary district of the Kyiv oblast. The colour of muscle tissue in the carcass was evaluated according to the method of the Japan Meat Grading Association. The total fat content, moisture content, and protein content of minced m. longissimus dorsi were analysed. Beef acidity (pH), penetration, and bound moisture content were also investigated. Consumer properties of beef were determined by tasting boiled meat (by aroma, juiciness, tenderness, ease of chewing) and broth from it (by colour, taste, thickness). It was found that the darker colour of muscle tissue had a likely (p>0.99) inverse correlation (r=-0.737) with beef boiling down. It showed a tendency for direct correlation with the cross-sectional area of back muscle (r=0.341), water binding capacity (r=0.326), penetration (r=0.295), adipose tissue colour (r=0.267), marbling (r=0.258), pH (r=0.231), and inverse correlation with mineral content (r=-0.309) and overall tasting score of cooked meat (r=-0.487). There was no correlation between muscle staining and the content of moisture, dry matter, protein, and fat (r= from -0.005 to 0.094). The practical significance of the study lies in the possibility of using the acquired knowledge to sort beef carcasses according to their purpose, and consumers will be provided with additional information for objective meat selection, considering the relationship between muscle colour and sensory and physical and technological properties of beef